Colorimetric approach to high-throughput mutation analysis. (April 2005) - Benoit, Nicole E.; Goldenberg, David; Deng, Shirley X.; Rosenbaum, Eli; Cohen, Yoram; Califano, Joseph A.; Shackelford, William H.; Wang, Xiao B.; Sidransky, David
High-throughput genomic mutation screening for primary tumors has characteristically been expensive, labor-intensive, and inadequate to detect low levels of mutation in a background of wild-type signal. We present a new, combined PCR and colorimetric approach that is inexpensive, simple, and can detect the presence of 1% mutation in a background of wild-type. We compared manual dideoxy sequencing of p53 for eight lung cancer samples to a novel assay combining a primer extension step and an enzymatic colorimetric step in a 96-well plate with covalently attached oligonucleotide sequences. For every sample, we were able to detect the presence or absence of the specific mutation with a statistically significant difference between the sample optical density (OD) and the background OD, with a sensitivity and specificity of 100%. This assay is straightforward, accurate, inexpensive, and allows for rapid, high-throughput analysis of samples, making it ideal for genomic mutation or polymorphism screening studies in both clinical and research settings.